5-Hydroxymethylcytosine alterations in the human postmortem brains of autism spectrum disorder. (22nd May 2018) - Cheng, Ying; Li, Ziyi; Manupipatpong, Sasicha; Lin, Li; Li, Xuekun; Xu, Tianlei; Jiang, Yong-Hui; Shu, Qiang; Wu, Hao; Jin, Peng
Abstract: Autism spectrum disorders (ASDs) include a group of syndromes characterized by impaired language, social and communication skills, in addition to restrictive behaviors or stereotypes. However, with a prevalence of 1.5% in developed countries and high comorbidity rates, no clear underlying mechanism that unifies the heterogeneous phenotypes of ASD exists. 5-hydroxymethylcytosine (5hmC) is highly enriched in the brain and recognized as an essential epigenetic mark in developmental and brain disorders. To explore the role of 5hmC in ASD, we used the genomic DNA isolated from the postmortem cerebellum of both ASD patients and age-matched controls to profile genome-wide distribution of 5hmC. We identified 797 age-dependent differentially hydroxymethylated regions (DhMRs) in the young group (age ≤ 18), while no significant DhMR was identified in the groups over 18 years of age. Pathway and disease association analyses demonstrated that the intragenic DhMRs were in the genes involved in cell–cell communication and neurological disorders. Also, we saw significant 5hmC changes in the larger group of psychiatric genes. Interestingly, we found that the predicted cis functions of non-coding intergenic DhMRs strikingly associate with ASD and intellectual disorders. A significant fraction of intergenic DhMRs overlapped with topologically associating domains. These results together suggest that 5hmC alteration is associated with ASD, particularly in the early development stage, and could contribute to the pathogenesis of ASD.